2008
DOI: 10.1289/ehp.10323
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inhaled Carbon Ultrafine Particles on Reactive Hyperemia in Healthy Human Subjects

Abstract: BackgroundUltrafine particles (UFP) may contribute to the cardiovascular effects of exposure to particulate air pollution, partly because of their relatively efficient alveolar deposition and potential to enter the pulmonary vascular space.ObjectivesThis study tested the hypothesis that inhalation of elemental carbon UFP alters systemic vascular function.MethodsSixteen healthy subjects (mean age, 26.9 ± 6.5 years) inhaled air or 50 μg/m3 elemental carbon UFP by mouthpiece for 2 hr, while exercising intermitten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
47
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 54 publications
4
47
1
Order By: Relevance
“…BP was also not affected. 407 Several recent studies have also shown that dilute diesel exhaust can impair peripheral resistance vessel responses to acetylcholine, bradykinin, and nitroprusside 6 hours after exposure. 384 The blunted responses to acetylcholine persisted for 24 hours in healthy adults.…”
Section: Vascular Dysfunctionmentioning
confidence: 99%
“…BP was also not affected. 407 Several recent studies have also shown that dilute diesel exhaust can impair peripheral resistance vessel responses to acetylcholine, bradykinin, and nitroprusside 6 hours after exposure. 384 The blunted responses to acetylcholine persisted for 24 hours in healthy adults.…”
Section: Vascular Dysfunctionmentioning
confidence: 99%
“…In particular, exposure to traffic has been shown to be a stronger risk for acute myocardial infarction and proximity to roadways is more strongly associated with coronary artery calcification than are indices of particulate matter respiratory exposure [18,19]. Although particulate matter has a definite toxic effect on the systemic vasculature in rodent models and in controlled human studies [20,21], environmental exposure to particulate matter never occurs without concomitant exposure to numerous gaseous co-pollutants. Diseases of the systemic vasculature can manifest in many ways, and we have a growing appreciation that particulate matter air pollution may exacerbate atherosclerosis [22], hypertension [23] and diabetic vasculopathy [24].…”
Section: Cardiovascular Effectsmentioning
confidence: 99%
“…It is because recent epidemiologic studies have shown UFPs are particularly relevant to pulmonary diseases, cancer, and mortality (Hoek et al 2002;Peters et al 2004;Delfino et al 2005Oberd€ orster et al 2005Br€ auner et al 2007;Shah et al 2008;Li et al 2010;Stewart et al 2010). The increased asthma prevalence is also found to often occur in the areas with high UFP level in ambient air or high motor vehicle traffic density, and in residence community nearby freeways (Samet et al 2000;Holguin 2008;Salam et al 2008;Patel and Miller, 2009).…”
Section: Introductionmentioning
confidence: 99%